The Effect of Simvastatin on Plasma Steroid Hormone Levels in Metformin-Treated Women with Non-Classic Congenital Adrenal Hyperplasia - Krysiak, R.; Kowalcze, K.; Bednarska-Czerwińska, A.; Okopień, B. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Non-classic congenital adrenal hyperplasia (NC-CAH), one of the most common genetic disorders, is often associated with the presence of hyperandrogenism. Recently both simvastatin and metformin were found to reduce plasma steroid hormone levels in this disorder. This study included 8 women with NC-CAH and diabetes or impaired glucose tolerance, as well as 12 matched women with similar glucose metabolism abnormalities but normal adrenal function. Both groups of women, receiving metformin for at least 6 months, were then treated with simvastatin (20 mg daily) for the following 12 weeks. Compared to patients with normal adrenal function, metformin-treated women with NC-CAH showed increased plasma levels of 17-hydroxyprogesterone, total testosterone, free testosterone, androstenedione and DHEA-S. Simvastatin reduced total and LDL cholesterol levels in both patients with NC-CAH and normal adrenal function. Moreover, in the former group of women, statin therapy decreased plasma levels of testosterone, free testosterone, androstenedione, dehydroepiandrosterone sulphate and tended to reduce 17-hydroxyprogesterone. Our results suggest that metformin-statin combination therapy may be useful in the management of symptomatic women with NC-CAH.
Keywords: congenital adrenal hyperplasia; metformin; statins; steroid hormones